1998
DOI: 10.1002/(sici)1096-9861(19980504)394:2<171::aid-cne3>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Organisation of the tectorotundal and SP/IPS‐rotundal projections in the chick

Abstract: The organisation of the neural projections from the optic tectum and pretectal nuclei complex, n. subpretectalis / n. interstitio-pretecto-subpretectalis (SP/IPS), to the nucleus rotundus (Rt) in chicks was studied by using retrograde tracing techniques. After the injection of fluorescent retrograde tracers, rhodamine-conjugated latex microspheres, fluorescein-conjugated latex microspheres, True Blue, Fluoro-Gold, or rhodamine B isothiocyanate, into different regions of Rt and its middorsal extension, the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 45 publications
2
51
0
Order By: Relevance
“…4C; n=3). The projection of the tectal efferent axons indicated that the labeled axons constitute the tectofugal pathway, and these axons had tectorotundal projections (Deng and Rogers, 1998;Wu et al, 2000;Puelles et al, 2007;Fedtsova et al, 2008). Next, we labeled tectal cells with GFP and mCherry-Nuc to follow the tangentially migrating cells.…”
Section: Movement Of Tangential Cell Migration Along the Tectal Effermentioning
confidence: 99%
“…4C; n=3). The projection of the tectal efferent axons indicated that the labeled axons constitute the tectofugal pathway, and these axons had tectorotundal projections (Deng and Rogers, 1998;Wu et al, 2000;Puelles et al, 2007;Fedtsova et al, 2008). Next, we labeled tectal cells with GFP and mCherry-Nuc to follow the tangentially migrating cells.…”
Section: Movement Of Tangential Cell Migration Along the Tectal Effermentioning
confidence: 99%
“…Reversed lateralization patterns after lesions of the tectotectal commissure [8] indicate that the actual functional lateralization pattern depends on a dynamic balance between left and right tectal processing [18]. Another modulator of the lateralized processing could be the tectorotundal system, which is modulated by the bed nuclei of the tecto-thalamic tract, the largest of which is the SP (nucleus subpretectalis) [2,21] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of degree of tectal differentiation, turtles and lacertomorph (type 1) lizards, on one hand, and birds, on the other, can be considered as the two extremes in the organization of tectothalamic projections. In birds, which have a very highly differentiated optic tectum, tectorotundal projection neurons are restricted to the SGC, with insignificant contribution from the SGFS (Benowitz and Karten, 1976; Hunt and Künzle, 1976; Karten et al, 1997; Deng and Rogers, 1998; Luksch et al, 1998; Hellmann and Güntürkün, 1999, 2001), whereas the neurons projecting to the nucleus opticus principalis (NOP; the homologue of the reptilian and mammalian GLd) are located exclusively in the SGFS (Wild, 1989; Deng and Rogers, 1998).…”
Section: Discussionmentioning
confidence: 99%